2007
DOI: 10.1090/s0025-5718-07-01990-4
|View full text |Cite
|
Sign up to set email alerts
|

Odd perfect numbers have at least nine distinct prime factors

Abstract: Abstract. An odd perfect number, N , is shown to have at least nine distinct prime factors. If 3 N then N must have at least twelve distinct prime divisors. The proof ultimately avoids previous computational results for odd perfect numbers.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
48
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(48 citation statements)
references
References 22 publications
0
48
0
Order By: Relevance
“…These pairs also arise in Mihȃilescu's solution of Catalan's problem [19,20], which asked if 8 and 9 are the only consecutive powers (indeed they are). Wieferich pairs appear as well in recent work on the question of the existence of odd perfect numbers [23], probably the oldest unsolved problem in mathematics.…”
Section: Introductionmentioning
confidence: 92%
See 1 more Smart Citation
“…These pairs also arise in Mihȃilescu's solution of Catalan's problem [19,20], which asked if 8 and 9 are the only consecutive powers (indeed they are). Wieferich pairs appear as well in recent work on the question of the existence of odd perfect numbers [23], probably the oldest unsolved problem in mathematics.…”
Section: Introductionmentioning
confidence: 92%
“…The first pair in (19), where q = 17, is of interest in the odd perfect number problem. In recent work on that question [23], Wieferich prime pairs in which the base q is a small Fermat prime are of some significance. (Recall that a Fermat prime is a prime number of the form 2 2 m + 1.)…”
Section: Wieferich Prime Pairsmentioning
confidence: 99%
“…It is easy to see that t > 0. (In fact, Nielsen [7] has recently shown that t 8.) We refer to the p a i i as components and to p 0 as the special prime in the factorization of N .…”
Section: On Odd Perfect Numbersmentioning
confidence: 99%
“…His work easily implies corresponding upper bounds in Theorems 1, 2, and 5. For the specific case of odd perfect numbers, one has the following effective version of Theorem 1, which is a sharpening due to Nielsen [25] of a theorem of Heath-Brown [18]. If N is odd perfect and ω(N ) ≤ k, then N < 2 4 k .…”
Section: Proposition 7 (Thābit's Rule)mentioning
confidence: 99%